PRACTICAL TRAINING: MATRIX TECHNOLOGY OF ORGANIZATION - Ksenia L. Polupan (Высшее образование в России)
The article analyzes legal and methodological materials, which standardize the process of organization and carrying out of student practical training. The author classifies theoretical approaches to practical training design, matrix technology of its organization, and presents the main ways of implementing the suggested approaches on the example of bachelor training in the field of Pedagogical Education (code: 44.03.01).